Arah Baru Kebijakan Publik: Studi Kasus Pemberdayaan Zakat - Angga Marzuki; Ibnu Qomar (Jurnal Bimas Islam, 2015)
Abstract Public policy is no longer understood as changingobligation. Public policy is interpreted as an effort to provide services, development and strengthening of community life. Through good public policy, each oriented program on public satisfaction and excellent service. Including in the management of zakat, the government has issued a policy steps and phases to realize the noble ideals of economic alleviation of the people. Through public policies oriented to the satisfaction of the public, the government has stepped away to formulate, to implement and to evaluate the implementation of zakat management with community involvement. Abstraksi Kebijakan publik tidak lagi dimaknai sebagai penggugur kewajiban. Kebijakan publik dimaknai sebagai upaya menghadirkan pelayanan, pembinaan dan penguatan kehidupan masyarakat. Melalui kebijakan publik yang baik, setiap program berorientasi pada kepuasan publik dan pelayanan prima. Termasuk dalam hal pengelolaan zakat, pemerintah telah mengeluarkan langkah dan kebijakan sebagai tahapan mewujudkan cita-cita mulia pengentasan ekonomi umat. Melalui kebijakan publik yang berorientasi pada kepuasan publik, pemerintah telah melangkah jauh merumuskan, melaksanakan dan mengevaluasi pelaksanaan pengelolaan zakat dengan melibatkan masyarakat. Keywords: public policy, zakat/charity, participation